Strength is in engagement: The rise of an online scientific community during the COVID‐19 pandemic. (5th May 2021) - Cucinotta, Christine E; Martin, Benjamin J E; Noé González, Melvin; Raman, Pravrutha; Teif, Vladimir B; Vlaming, Hanneke
Abstract : Many scientists, confined to home office by COVID‐19, have been gathering in online communities, which could become viable alternatives to physical meetings and conferences.